Designing for cohesive project implementations enhancing corporate & thematic identities - Santaromana, Francis L. (Muhon : Journal of Architecture, Landscape Architecture, and the Designed Environment, 2005)
Buildings of integral development TALK, and are INTERACTIVE not only in function but by virtual images as well. It cannot be ignored that opportunities of impact exist and add value to the greater recall. These are not just limited to qualitative assessment but are quantifiable if appropriate tools and benchmarks are applied. A new language to justifiable creative investment is defined as well as a reference to INFORMED decision making.